(untitled) (Colloquia Comparativa Litterarum, 2025)
The text focuses on several recently published novels and a book of essays, which have provoked reactions and debates both in Bulgaria and around the world. It tries to see how writers rationalize the pandemic at the very beginning of its emergence. For most authors topics such as politics and ecology are important, because according to them the Covid crisis is the result of all other crises of today’s world, and most of all, of the irresponsible human attitude towards nature and other human beings. Not accidentally – in their visions – it heralds new changes in the human and in the acceleration of the dystopian wave in literature.